A New Search for and Old Russia: Contemporary Russian Research on the Kievan and "Partition" Periods of Russian History - Komendová, Jitka (Dějiny – teorie – kritika, 2024)
The aim of this study is to provide an elementary overview of contemporary Russian research on the history of Russia up until the 15th century and to present some of the issues to which contemporary Russian medieval studies is currently devoting itself. After a period of enforced isolation, Russian scholars in the 1990s began concerning themselves intensively with the methodologies used in Western medieval studies and has been trying to apply them to Eastern European historical material which Western medieval studies has heretofore – with rare exceptions – largely ignored. Following the establishment of democracy in academia, the need to revise the landscape of the history of the Russia of the Kievan and "partition" periods became apparent. However, due to the character of Russian sources, it is not possible in any simple way to transfer the methods used in working with Western medieval materials to the study of these periods. This is why the new historical fields have devoted themselves primarily to the 16th and 17th centuries, which provide the richest and most varied sources materials. Although it is certain that Russian medieval studies has succeeded in overcoming the crisis it experienced in the 1990s, one of the central problems afflicting contemporary Russian and Western medieval studies remains: the absolute separation between research on the middle ages in Russia and in Western and indeed in Central Europe.